Analisis Faktor-Faktor Yang Berhubungan Dengan Perilaku Masyarakat Kota Tasikmalaya Dalam Pengelolaan Sampah Rumah Tangga Di Masa Pandemi Covid-19 - Teni Supriyani; Isyeu Sriagustini (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2022)
Household waste is the largest producer of waste from total waste in Indonesia. Waste production in Tasikmalaya City is 156 tons of waste/day and 75% of it is household waste. Awareness of household waste management < 1%, which affects the landfill which is predicted to only leave space for 4-5 more years. In the middle of the Covid-19 pandemic, there is an increase in household waste. The aim of this study was to determine the factors related to the behavior of the people of Tasikmalaya City in managing household waste during the Covid-19 pandemic. This type of research is quantitative research with a cross-sectional approach. The study population was all residents of the City of Tasikmalaya aged > 15 years. The research sample is the residents of the City of Tasikmalaya who are > 15 years old and are willing to fill out an online questionnaire. The sampling technique was accidental sampling, with a minimum number of samples (n). The dependent variable is household waste, the independent variables are age, gender, education level, family income, daily expenses for food, activity base from home, online shopping habits, and the availability of trash bins. The results showed 56.9% of the people of Tasikmalaya City stated that the volume of their household waste during the pandemic was the same as before the Covid-19 pandemic. The results also found a significant relationship between online shopping/buying food habits and the volume of household waste during the pandemic (p=0.018; OR 1.830; 95% CI: 1.106-3.027). People who have the habit of shopping/buying food online during the pandemic have a 1,830 greater tendency to generate more volume of waste compared to people who are not accustomed to buying food online during the pandemic.